PREOPERATIVE KETOROLAC EFFECT ON POSTOPERATIVE PAIN ON TURP PATIENTS - Hadi, Choirul; Utomo, Trisula (Indonesian Urological Association, 2013)
Objective: The aim of this study is to study the effect of preoperative Ketorolac on postoperative pain after transurethral prostatectomy at Sardjito Hospital Yogyakarta. Material & Methods: This is a cross sectional, analytic, prospective study. We divided benign prostatic hyperplasia patients, from October 2011 until February 2012 into two groups. Group I was given Ketorolac 30 mg intravenously twice daily starting one day before operation and in the morning before procedure. Group II did not receive Ketorolac preoperatively. Patients underwent transurethral operation with spinal anesthesia. We assessed postoperative pain at 24 hours using Visual Analogue Scale (VAS). Results: Twenty four patients were included in this study with mean age 66 years old with the youngest 45 years old and the oldest 80 years old (SD 8,77744). Group I (17 patients), VAS score 1 to 7 with median 3 and mean 3,4118 (SD 1,66053). Group II (7 patients) VAS score 1 to 8 with median 3 and mean 3,8571 (SD 2,8357). We count it using Mann-Whitney U (p = 0,951). Conclusion: There is no significance difference in post-operative pain after transurethral prostatectomy with preoperative ketorolac administration.Keywords: Ketorolac, bupivacaine, visual analogue scale, transurethral prostatectomy.